Functional characterization of the three Oryza sativa SPX‐MFS proteins in maintaining phosphate homoeostasis. (17th August 2022) - Guo, Runze; Zhang, Qi; Ying, Yinghui; Liao, Wenying; Liu, Yu; Whelan, James; Chuanzao, Mao; Shou, Huixia
Abstract: Plant vacuoles serve as the primary intracellular compartments for phosphorus (P) storage. The Oryza sativa genome contains three genes that encode SPX ( S YG1/ P HO81/ X PR1)‐MFS ( M ajor F acility S uperfamily) proteins (OsSPX‐MFS1‐3). The physiological roles of the three transporters under varying P conditions in laboratory and field are not known. To address this knowledge gap, we generated single, double and triple mutants for three Os SPX‐MFS genes. All the mutants except Osspx‐mfs2 display lower vacuolar Pi concentrations and Os SPX‐MFSs overexpression plant display higher Pi accumulation, demonstrating that all OsSPX‐MFSs are vacuolar Pi influx transporters. OsSPX‐MFS3 plays the dominant role based on the phenotypes of single mutants in terms of growth, vacuolar and tissue Pi concentrations. OsSPX‐MFS2 is the weakest and only functions as vacuole Pi sequestration in an Osspx‐mfs1/3 background. The vacuolar Pi sequestration capacity was severely impaired in Osspx‐mfs1 / 3 and Osspx‐mfs1 /2/ 3, which resulted in increased Pi allocation to aerial organs. High P in the panicle impaired panicle and fertility in Osspx‐mfs1 / 3 and Osspx‐mfs1 / 2 / 3 . Osspx‐mfs2 resulted in a more stable yield compared to the wild type under low P in field grown plants. The results suggest that alteration of vacuolar Pi sequestration may be a novel effective strategy to improve rice tolerance to low phosphorus in cropping systems.